Min tarikh al-aqtar al-'Arabiyah fi al-'ahd al-'Uthmani : buhuth wa-watha'iq wa-qawanin - Sahillioglu, Halil, 1924-; Research Centre for Islamic History, Art, and Culture (Istanbul : Munazzamat al-Mu'tamar al-Islami, Markaz al-Abhath lil-Tarikh wa-al-Funun wa-al-Thaqafah al-Islamiyah, Irsika, 2000)
Arab countries; Ottoman Empire era; history.
Includes bibliographical references.
Keywords: Finance, Public -- Arab countries -- History; Taxation -- Arab countries -- History; Arab countries -- History -- 1517-1918.